1996
DOI: 10.1093/oxfordjournals.aje.a008852
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Ferrtin, Iron Intake, and the Risk of Colorectal Polyps

Abstract: High iron exposure has been associated with colorectal neoplasia in several studies. The authors investigated plasma ferritin, an indicator of iron stores, and iron intake as risk factors for adenomatous polyps, intermediate markers for colorectal cancer. During 1991-1993, they collected fasting blood samples from and administered questionnaires to men and women 50-75 years old who visited free sigmoidoscopy clinics at a health maintenance organization. Data from 965 subjects (467 cases, 498 controls) were ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
59
1
1

Year Published

1999
1999
2007
2007

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(63 citation statements)
references
References 35 publications
2
59
1
1
Order By: Relevance
“…With greater variability of serum iron, a single measurement would include a large degree of measurement error and, as a consequence, observed association such as relative risk would be increasingly attenuated. Therefore, the low reliability coefficient of serum iron, as shown here, may contribute to the apparent discrepancies of the results observed in previous studies [15][16][17][18]20,21].…”
Section: Discussioncontrasting
confidence: 77%
See 1 more Smart Citation
“…With greater variability of serum iron, a single measurement would include a large degree of measurement error and, as a consequence, observed association such as relative risk would be increasingly attenuated. Therefore, the low reliability coefficient of serum iron, as shown here, may contribute to the apparent discrepancies of the results observed in previous studies [15][16][17][18]20,21].…”
Section: Discussioncontrasting
confidence: 77%
“…Although other studies reported either no association or an inverse association [17,18], this discrepancy may be due to the fact that the iron measured in these studies represents only a small fraction (<1%) of the total iron in the body [19]. Serum iron, which is the iron stored in transferrin, total iron-binding capacity, which is the total level of transferrin when 100% saturated with iron, and percentage saturation of transferrin were used as biological indices of body iron storage in these studies [15][16][17][18]20,21]. In contrast, ferritin, an iron storage protein, has rarely been measured.…”
Section: Introductionmentioning
confidence: 99%
“…Free iron is a pro-oxidant, and may contribute to colorectal carcinogenesis by promoting free radical production and lipid peroxidation (Nelson, 1992;Toyokuni, 1996;Huang, 2003). Epidemiologic studies examining the association of iron intake and markers of body iron stores with risk of colorectal cancer or colorectal polyps have yielded some evidence of positive associations (Knekt et al, 1994;Bird et al, 1996;Wurzelmann et al, 1996;Tseng et al, 1997;Kato et al, 1999). In addition, epidemiologic studies have shown a modest association between red meat intake, the major source of dietary iron, and risk of colon and colorectal cancer (Norat and Riboli, 2001;Larsson and Wolk, 2006).…”
mentioning
confidence: 99%
“…Our findings replicate an association with colon cancer but not rectal cancer in one earlier study, 37 whereas others have reported effects of iron on cancers of the rectum and distal colon. 33,39,40 It has been suggested that colon and rectal cancers have different etiologies, 41 although it is not clear why iron would only exert effects in specific sub-sites.…”
Section: Discussionmentioning
confidence: 99%